Developing and Validating an Innovative Vision Leadership Model for High School Directors in Cambodia - Tonghor Hab; Sarom Mok; Chumnor Lek (MASI Mandiri Edukasi, 2026)
An innovative vision is considered critical to school development, as it enables school directors to anticipate future outcomes and challenges and to inform strategic and operational planning. It can also be incorporated into the creation of the school's strategic plan and annual operational plan. The present study aimed to validate a scale that reflects innovative vision in high school. The study surveyed 820 teachers to assess their perceptions of the innovative vision of high school principals in the four Cambodian provinces, who were all asked to complete a survey on their perceptions of implementing the tasks of high school directors. This 5-point Likert scale assessed school directors' ability to create, implement, disseminate, and serve as role models in Cambodia. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were adopted in this study. The EFA results demonstrated that the scale contains four dimensions with good indicators with model fit χ2 (84) = 216.587, χ2/df=2.58, P < 0.001. Good model fits derived from CFA supported the four-dimensional structure. Further analysis revealed positive correlations between this scale and the other scales, indicating convergent validity. These findings confirmed that this scale is a reliable and valid tool for innovative vision in Cambodia. In future studies, researchers may extend its use in other educational levels by examining its reliability and validity.